2006
DOI: 10.1159/000098211
|View full text |Cite
|
Sign up to set email alerts
|

Possible Involvement of Oxidative Stress in Salivary Gland of Patients with Sjögren’s Syndrome

Abstract: Objective: To determine the involvement of oxidative stress in the salivary gland of patients with Sjögren’s syndrome (SS). Methods: Oxidative damage to the gland was measured by 8-hydroxy-2′-deoxyguanosine (8-OHdG) and hexanoyl-lysine (HEL) using the SS saliva. In addition, lactate dehydrogenase (LDH) and mitochondrial glutamic-oxaloacetic transaminase (m-GOT), both general markers for cell damage, were also analyzed. Results: Increased levels of 8-OHdG and HEL were found in the saliva of SS patients, but not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
76
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(80 citation statements)
references
References 99 publications
4
76
0
Order By: Relevance
“…In addition, increased levels of tissue 8-OHdG were found in the brain, heart, liver and kidney in the periodontal inflammation model. HEL and 8-OHdG are accepted as parameters of lipid peroxide and oxidative DNA damage, respectively (22). These results suggest that increased blood lipid peroxide following periodontal inflammation could induce oxidative DNA damage of the brain, heart, liver and kidney.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In addition, increased levels of tissue 8-OHdG were found in the brain, heart, liver and kidney in the periodontal inflammation model. HEL and 8-OHdG are accepted as parameters of lipid peroxide and oxidative DNA damage, respectively (22). These results suggest that increased blood lipid peroxide following periodontal inflammation could induce oxidative DNA damage of the brain, heart, liver and kidney.…”
Section: Discussionmentioning
confidence: 91%
“…The purpose of the present study was to examine whether the generation of lipid peroxide in periodontal inflammation could induce oxidative damage in the liver, heart, kidney and brain using a rat model. In order to evaluate lipid peroxide, the level of hexanoyl-lysine (HEL) was determined (22). In addition, the serum level of C-reactive protein (CRP) was measured because previous studies indicated that periodontal inflammation results in low-grade systemic inflammation (7,9,16).…”
mentioning
confidence: 99%
“…Sjögren's syndrome (Fox, 2005;Ryo et al, 2006). These findings suggest that oxidative stress from ROS causes salivary gland dysfunction (Vitolo et al, 2004).…”
mentioning
confidence: 93%
“…periodontitis) and systemic (e.g. diabetes, inflammatory bowel disease) conditions (Arana et al 2006;Bahar et al 2007;Celec et al 2005;Gorelik et al 2007;Jahanshahi et al 2004;Kolarzyk et al 2006;Mashayekhi et al 2005;Nagler et al 2000;Reznick et al 2006;Ryo et al 2006;Sawamoto et al 2005;Sculley and Langley-Evans 2003;Sugano et al 2003;Takane et al 2002;Tsai et al 2005). Changes in salivary cortisol secretion patterns (Fiocco et al 2006;Giubilei et al 2001;Hatfield et al 2004;Porter et al 2002;Scherder et al 2006;Wolf et al 2002;Woods and Dimond 2002), amylase activity (Sramek et al 1995), and acetylcholinesterase activity (Sayer et al 2004) have been documented in persons with AD or MCI, attesting to the plausibility of exploiting saliva for neurodegenerative disease biomarker discovery.…”
Section: Introductionmentioning
confidence: 99%